A thematic analysis of flu vaccine hesitance in ethnically minoritised communities in Liverpool - Anna Powell; Marie Claire Van Hout; Deborah Connors; Catharine Montgomery (PLoS ONE, 2025)
Background Seasonal influenza causes around 15,000 deaths yearly in the United Kingdom. Low vaccine uptake is more prominent in ethnically minoritised communities and deprived areas, leading to poorer outcomes. Aims To understand influenza vaccine hesitance in ethnically minoritised communities in Liverpool from multistakeholder perspectives. Methods Semi-structured interviews and focus groups were conducted with members of the public (n = 55), community engagement workers (n = 14), primary healthcare staff (n = 20), and policy professionals (n = 10). Data were analysed thematically. Results Six themes were identified. Beliefs about vaccine safety, necessity, and efficacy often arose from misinformation, misunderstanding, or negative experience. Trust in vaccine information depended on source familiarity, credibility, and perceived intentions, while trust in the healthcare system had decreased due to cultural and COVID-19 concerns. Accessibility of accurate vaccine information was poor, due to language and literacy barriers. Community opinions/experience shaped perceptions, while community organisations were trusted but needed resources/stability. Healthcare staff described low morale, time/resource constraints, and uncertainty in addressing cultural concerns. Ultimately, Alliance indicated a desire for better integration between healthcare and communities, particularly for developing/distributing accurate, culturally relevant, and accessible information. Conclusion To address influenza vaccine hesitance, stakeholders should collaborate to improve access to reliable information (to support development of pro-vaccine beliefs) via tailored communication and culturally informed training for healthcare staff; aim to increase trust by, for example, ensuring access to familiar staff and employing community members; and foster alliance via long-term support of community organisations through funding, accurate information, and training.